A new technique for evaluating Southwestern corn borer damage to post-anthesis maize - Davis, F.M.=700 1 Williams, W.P.
Sumario (En)
Ilus.; 8 ref.
Keywords: ZEA MAYS; RESISTENCIA A LAS PLAGAS; EVALUACION; DAÑOS; DIATRAEA GRANDIOSELLA